تأثير الخمولية على مقاومة التآكل لأسطح الفولاذ المنخفض الكربون - موسى المحمد (Tishreen University, 2019)
الهدف من الدراسة تحسين خمولية وزيادة مقاومة التآكل لأحد أنواع الفولاذ المنخفض الكربون المحتوي على 0.15% كربون المستخدم محليا في تصنيع بعض عناصر الآلات. الدراسة تضمنت تحضير عينات الفولاذ المنخفض الكربون، بإبعاد (20*10 سم ) وبسماكة 2.5 مم. العينات تم غمرها في محلول يحوي الأتي: الصودا الكاوية، نترات الصوديوم (2%)، كرومات الصوديوم (2.5%). درس تأثير كل من تركيز الصودا الكاوية ودرجة الحرارة  وزمن غمر على معدل تآكل العينات. أظهرت النتائج بان أفضل خمولية للسطوح يمكن الحصول عليها عند 5% (الصودا الكاوية) و مدة غمر (30 دقيقة) ودرجة حرارة محلول الغمر (46 درجة مئوية). أيضا، أظهرت النتائج تحسن ملحوظ في مقاومة التآكل والصدأ للفولاذ المستخدم لمدة تزيد عن 180 يوم. This study aims to improve the passivity and increase corrosion resistance on one of low carbon steel containing 0.15%C locally used in manufacturing some of machine elements. The study includes preparing specimens of low carbon steel, with (10*20 cm) dimension and its (2.5 mm) thickness. The specimens were immersed in a solution containing the following: Caustic soda, Sodium nitrate (2%), Sodium chromate (2.5%). The influence of caustic soda concentrations, temperature of solution and time of immersing on corrosion rate of specimens were studied. The results show that the best passive surfaces can be obtained with caustic soda concentration (5%), time of immersing specimens (30 min) and temperature of solution (46oC). The results also show noticeable improvement in the corrosion resistance of the metal used for more than 180 days.